Quantification of freshness loss and an optimization approach for managing fresh fruit exportation - Kamhangwong Damrongpol (2018)
© 2016 IEEE. An integrative view on logistics and product quality is one of keys to supply chain management for the fresh food industry. As it is difficult to define quality deterioration during distribution and incorporate it into logistics cost model, a quality loss assessment in term of freshness loss and a simple modelling approach to maximize net profit is proposed in this study. Export of Mangosteen from Thailand to China has been selected to be a case study and to develop the proposed model with varying environmental condition of storage and transportation, and quantity of supply and demand. The resulting model can be applied in an illustrative case study for the other fresh produce, and it can be used to plan and operate fruit exportation in term of production, distribution and inventory planning.